2020
DOI: 10.1186/s12868-020-00587-z
|View full text |Cite
|
Sign up to set email alerts
|

Autoreceptor control of serotonin dynamics

Abstract: Background Serotonin is a neurotransmitter that has been linked to a wide variety of behaviors including feeding and body-weight regulation, social hierarchies, aggression and suicidality, obsessive compulsive disorder, alcoholism, anxiety, and affective disorders. Full understanding involves genomics, neurochemistry, electrophysiology, and behavior. The scientific issues are daunting but important for human health because of the use of selective serotonin reuptake inhibitors and other pharmaco… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
17
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 8 publications
(17 citation statements)
references
References 92 publications
0
17
0
Order By: Relevance
“…We have developed and parameterized a dynamic model to test the impact of elevated cortisol/ corticosterone levels and their consequences on serotonin, dopamine and kynurenine pathways, which are known to be associated with the etiology of MDD. Previous models have investigated the interplay of dopaminergic and serotonergic pathways in different contexts, such as the influence of firing and the roles of autoreceptors [47][48][49][50]. However, to the best of our knowledge, this is the first mathematical model integrating all pertinent biochemical pathways into a model of depression.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…We have developed and parameterized a dynamic model to test the impact of elevated cortisol/ corticosterone levels and their consequences on serotonin, dopamine and kynurenine pathways, which are known to be associated with the etiology of MDD. Previous models have investigated the interplay of dopaminergic and serotonergic pathways in different contexts, such as the influence of firing and the roles of autoreceptors [47][48][49][50]. However, to the best of our knowledge, this is the first mathematical model integrating all pertinent biochemical pathways into a model of depression.…”
Section: Discussionmentioning
confidence: 99%
“…e ., > 100%) were adjusted based on data from experiments on chronic stress in animal models (see Table C in S2 Supplement ). Finally, the rate constants were calculated for the final set of power-law equations according to the methodology described in [ 30 ] and based on the flux partitioning ratios taken from other models in the literature [ 33 , 47 50 , 79 , 155 ].…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…As discussed in Section 3, the experimental results in [11] and later papers revealed that various aspects of the 2010 model were naive and too simplistic. So, in 2020, the authors and collaborators expanded and revised the original model to take account of the new findings that we had learned [13]. Here we will briefly discuss the changes and some of the new results.…”
Section: Autoreceptor Variable Dynamics In the Model After Stimulation Release Of Histamine Causes Extracellular Histamine To Rise And Thmentioning
confidence: 99%
“…That paper changed our understanding of 5-HT 1b autoreceptors and showed that the way we modeled autoreceptors in 2010 [5] was wrong. Section 4 describes our 2017 paper [12] creating a mathematical model for histamine dynamics in the brain and Section 5 discusses our 2020 paper [13] revising and expanding our original 5-HT model. In Section 6 we briefly describe the techniques for measuring 5-HT and histamine in the extracellular space and in Section 7 we describe our ideas and speculations about depression.…”
Section: Introductionmentioning
confidence: 99%